Characterization of nanotubular oxide layer grown on Ti14wt.%Nb alloy by anodization and its performance in photoelectrocatalytic process - Santos, Daniely Reis [UNESP] (2020)
The development and application of well-organized nanostructured materials with high absorption on visible light for application in photoelectrodegradation of polluting organic compounds are challenging problems. This paper presents the formation of nanotubular oxides grown on Ti14wt.%Nb substrate (NT/Ti14wt.%Nb) by an anodizing process, as well as the influence of the temperature in the oxide crystallization and in the photocatalytic activity performance. The oxide layers were characterized by SEM, EDX, Raman, XRD, and photocurrent studies. Electrochemical impedance spectroscopy measurements and polarization curves were also investigated. The diffusion reflectance UV-Vis-NIR spectroscopy assays showed higher absorption in the visible region for Nb-modified TiO2 nanotubes. The characterization of the nanoscale oxide layer grown on Ti14wt.%Nb alloy showed a hybrid (partially Nb-doped) semiconductor behavior with high current density under UV/visible and visible light. Besides that, NT/Ti14wt.%Nb demonstrated greater resistance to corrosion and low recombination of charges compared with TiO2 nanotubes. In general, the results have shown that NT/Ti14wt.%Nb presents a potential for its application in photoelectrocatalytic (PEC) degradation processes. PEC tests of the Reactive Blue 4 (RB4) dye showed total decoloration (k = 0.17 min−1) and 88% degradation under UV/visible light for the oxide layer grown on Ti14wt.%Nb alloy annealed at 450 °C in comparison with those for the oxide layer grown on TiO2 nanotubes.